(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Abstract: This research is aim to achieve the following: 1. State that the growth of the units can’t alone form a goal, it must be matched with the actual capacities of those units and the conditions for obtaining any funds that could finance such growth. 2. State the role of sustainable growth rate in predicating the financial failure of the units for the samples related to this research, and investigate the efficiency of using a model to predict the financial failure of these units. 3. Provide an indication to those who are interested in predicting financial failure to the units, by measuring and analyzing the actual and sustainable growth rate for the units, rather than relying on financial ratios and predictability models of failure. The population of research is represent the contributed and listed units in the Iraqi stock exchange, and the samples was chosen randomly, consists 20 contribution units for the period from 2009-2015, about 29% from the research population. The major findings for this research, despite of the weak of the statistical relationship between the rate of sustainable growth and financial failure for companies, or lack of relationship, however, the sustainable growth rate could predict 50% of the studied units, 45% of which represent losing companies (9 Companies), and the other 5% represent profitable company (Iraqi Company for Carpets and Furniture), because it was growing within its sustainable growth rate. Based on this research, it is necessary to recommend the units to make their investment and financing decisions within the well-considered financial strategy in line with the overall strategy of the unit, therefore, make these decisions in light with its impacts on the targeted growth strategy. Therefore, it’s necessary alike to the small, medium and large business owners to calculate their sustainable growth, and use it to determine if they have sufficient cash to meet their strategic growth needs